PEMBUATAN PETA ALIH FUNGSI LAHAN DESA JAYAMULYA TAHUN 2013-2023 - Rani, Dewi; Sulastri, Tuti; Rofieq, Ainur (Universitas Islam 45 Bekasi, 2024)
Jayamulya Village is one of the villages located in Serang Baru Sub-district, Bekasi Regency and is a fairly densely populated area today. Therefore, a lot of development is carried out and will result in significant land changes. Thus, the implementation of community service related to making a map of land use change in Jayamulya Village in 2013-2023 using the ArcGIS 10.8 application. This activity was carried out with the aim of providing information and an overview of what happened to an area that previously could be an agricultural area, namely rice fields, and turned into a residential area. The data will be processed using supervised techniques in the ArcGIS 10.8 application, after which the map will be socialised to village officials. This land use change map making programme in Jayamulya Village is one way to conduct regular monitoring so that it can see changes in land area that have been updated at this time.